SEMANTIC ANALYSIS; JARGON AND WORDS WITH SPECIFIC MEANING USED IN MOTOGP - Thifal Fayi; Sari Rejeki; Ni Made Widisanti (Journal Albion : Journal of English Literature, Language, and Culture, 2021)
This study aims to identify the jargon and specific meaning used by the professionals and community of MotoGP such as commentators and hosts (during MotoGP race), interviewers (during interviews) and racers (during interviews) taken from YouTube in the period of March-November 2019. This research is descriptive-qualitative in nature. The results of the study reveal, out of 64, 33 words are categorized as jargons and 31 words have specific meaning. The jargon and words which specific meaning found in the sport of MotoGP racing all refer to the racing technique, the situation and conditions of the riders, the communication between the teams and groups of the event, as well as the conditions of the race track in competitions. Keywords : Jargon; specific meaning; MotoGP